A Comprehensive Study of Dynamic Response of High-Rise Buildings Under the Influence of Shear Walls (International Journal of Innovative Research in Engineering & Management, 2022)
Buildings undergo a lot of vibrations at  the time of earthquakes or strong winds acting upon it.  These vibrations make the building more prone to  damages and create a sort of fear psychosis among the  people residing in it. Thus, buildings need to be first  analyzed for these vibrations, so as to design the building in such a way that its vibrations produced are minimized  to a large extend, thereby eliminating the fear psychosis  of people and making the building safer. High rise buildings undergo much more vibrations and lateral drifts as compared to low height buildings. Thus tall buildings are provided with shear walls to counteract and minimize  the effect of lateral loads acting on the structure. The  properties of these seismic shear walls dominate the response of the buildings, and therefore, it is important to evaluate the seismic response of the walls  appropriately. In this present study, main focus is to determine the  solution for shear wall location in high rise building and  to cater the vibrations of the buildings produced due to  lateral loading acting on the floors. In this project  dynamic behavior of the building is to be studied carefully, so as to reduce the lateral drifts produced in the  building and thus making the building resistant to the lateral loads. STAAD-Pro V8i software will be used to perform allthe parametric study analysis of these lateral  loads upon the structure. Complicated and high-rise structures need very time taking and cumbersome calculations using conventional manual methods.  STAAD-Pro provides us a fast, efficient, easy to use and  accurate platform for analysing and designing structure.  In this study different models were studied on the basisof  different positions of shear walls, out of which model 4  (with lift core wall and shear wall at corners) showed better performance in regarding all the parameters of study which included storey drifts, base shear, frequency  and axial forces. Two methods were taken for the analysis out of which response spectrum method showed better and precise results.
Keywords: Shear Wall; Lift Core Wall; Storey Drift; Base Shear; High Rise Building; Lateral Drift; Staad-Pro V8i